2001
DOI: 10.1038/ng811
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning of the combined hyperlipidemia gene Hyplip1

Abstract: Familial combined hyperlipidemia (FCHL, MIM-144250) is a common, multifactorial and heterogeneous dyslipidemia predisposing to premature coronary artery disease and characterized by elevated plasma triglycerides, cholesterol, or both. We identified a mutant mouse strain, HcB-19/Dem (HcB-19), that shares features with FCHL, including hypertriglyceridemia, hypercholesterolemia, elevated plasma apolipoprotein B and increased secretion of triglyceride-rich lipoproteins. The hyperlipidemia results from spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
179
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(190 citation statements)
references
References 27 publications
8
179
1
1
Order By: Relevance
“…As a matter of fact, it has been reported that nuclear Trx are helpful for TNF-␣-induced activation of NF-B, a proinflammatory and procarcinogenic transcription factor Karin and Greten, 2005). In addition, the drug-resistance of cancer due to higher expression of thioredoxin (Sasada et al, 1996) and previously reported hyperlipidemic phenotype of the Txnip-deficient mice (Bodnar et al, 2002) are probably the two other examples of such detrimental effect of Trx system. In summary, this study suggests that besides its antioxidant function in maintenance of cellular redox homeostasis, Trx may act as a regulator for timely quenching excessive PPAR␣ signaling and controlling the expression levels of PPAR␣-regulated metabolic enzymes according to metabolic need.…”
Section: Discussionmentioning
confidence: 98%
“…As a matter of fact, it has been reported that nuclear Trx are helpful for TNF-␣-induced activation of NF-B, a proinflammatory and procarcinogenic transcription factor Karin and Greten, 2005). In addition, the drug-resistance of cancer due to higher expression of thioredoxin (Sasada et al, 1996) and previously reported hyperlipidemic phenotype of the Txnip-deficient mice (Bodnar et al, 2002) are probably the two other examples of such detrimental effect of Trx system. In summary, this study suggests that besides its antioxidant function in maintenance of cellular redox homeostasis, Trx may act as a regulator for timely quenching excessive PPAR␣ signaling and controlling the expression levels of PPAR␣-regulated metabolic enzymes according to metabolic need.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6]. We excluded TXNIP, a causative gene for combined hyperlipidemia in mice 13 , and found that USF1 had significant association, linkage and shared haplotypes of the disease-associated alleles. The strongest evidence for association was Table 3 Haplotype analyses in men with elevated triglyceride levels using HBAT The inter-SNP distances and corresponding rs numbers for the SNPs f11r1s4-f11r1s6 and usf1s1-usf1s5 are shown in Table 2.…”
mentioning
confidence: 99%
“…Response to pest/pathogen/ parasite (13) Immune response (16) Response to external stimulus (17) Response to wounding (9) Upregulated genes Downregulated genes Figure 2 Distribution of genes according to functional category for the 16 upregulated and 60 downregulated genes for which annotation information for the Gene Ontology 26 class Biological process was available. In this analysis, lists of differentially expressed genes were examined for overrepresentation of functional classes, as defined by the Gene Ontology consortium, using the EASE tool 27 .…”
mentioning
confidence: 99%
“…21,22 In 1999, we identified a Trx-binding protein with a yeast two-hybrid assay and named it Trx-binding protein-2 (TBP-2); 23 it was recognized that TBP-2 is identical to vitamin D 3 upregulated protein-1 (VDUP-1) 24 or thioredoxin-interacting protein. 25 In a more recent work, we found that loss of TBP-2 plays an important role in human T-cell leukemia virus type I-induced T-cell transformation. 26 In the present study, we examined the significance of TBP-2 in the Fe-NTA-induced renal cancer model of rats.…”
mentioning
confidence: 99%